Pengaruh Pemberian Insentif Terhadap Komitmen Kerja Karyawan di Rumah Sakit Umum Bethesda Kota Tomohon - Sjeddie Rianne Watung; Febryani M. L. Rattu; Shelty Deity M Sumual; Jerry Rommy Herter Wuisang (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2021)
The provision of incentives is one stimulus to encourage someone’s loyalty, and better work performance as the incentives are paid based on one’s work commitment. This research was conducted at Bethesda General Hospital, Tomohon City, and aims to determine the effect of incentives on its employee work commitment. The results of the correlation coefficient analysis of r = 0.84 indicated that there is a close and positive relationship between incentives and employee work commitment. The correlation analysis also produced the coefficient of determination r² = 0.71 or 71%, implying that the provision of incentives influences 71% of employee work commitment, and other factors beyond this research influence the remaining 29%. In addition, the t-test analysis shows that t count = 8.23 is greater than t table = 1.70 indicating a highly significant relationship between the provision of incentives and employee work commitment.